(untitled) (Annals of Bangladesh Agriculture, 2022)
Reactive oxygen species (ROS) generated in various metabolic reactions in plants are mostly known for toxicity. Whereas ascorbic acid (AsA) involves in various physiological and biochemical processes; and acts as a ROS scavenger. Therefore, the experiment was conducted to investigate the effects of exogenous application of AsA on growth and yield of tomato plants. The ROS scavenger AsA was applied in the leaves of tomato plants in four treatment combinations (T1-Control; T2-0.5 mM; T3-2.0 mM and T4-4.0 mM) with three replications. Among the treatments, AsA at 4.0 mM (T4) efficiently increased leaf length (12%), inflorescence length (17%), and flower number (29%) than the untreated control plants. AsA at 0.5 and 2.0 mM also showed positive effects on the plant morphology to a lesser extent. Importantly, AsA at 4.0 mM increased yield by 18% than the control treatment. In physiochemical parameters, AsA at 4.0 mM (T4) was retained 64.07% higher chlorophyll content than the control plant even after 60 days of application. Exogenous application of AsA effectively reduced oxidative stress of the plant, which was attributed to the less accumulation of H2O2 and lipid peroxidation of membrane lipids. AsA at 4.0 mM decreased H2O2 and MDA accumulation by 39% and 45%, respectively, compared with the control plants. Therefore, exogenous application of AsA is a useful tool to enhance growth and yield of tomato under field conditions by lowering the accumulation of ROS and lipid peroxidation. Ann. Bangladesh Agric. (2021) 25 (1) : 55-65